Tratamiento Covid-19 - Hunt P, Nicole; Bastías O, Carla (Revista Hospital Clínico Universidad de Chile, 2021)
The main treatment for patients with severe Covid-19 is to maintain adequate ventilatory support and monitor the possible progression of the disease. Therapeutic strategies such as High Flow Nasal Cannula, awake prone position, antithrombotic prophylaxis and the use of dexamethasone. There have improved the probability of not presenting complications and not requiring invasive mechanical ventilation. The use of convalescent plasma is still under investigation and is currently only recommended in clinical trials. Finding antivirals that allow treating the infection and clinically improving patients has led to mounting studies with different methodologies, and currently there are specific and limited indications for their routine use, as in the case of Remdesivir, which has been approved by the FDA as emergency treatment in severe cases. Immunomodulatory treatments are still under study. An example of this is Tocilizumab and Anakinra, which have shown promising results for the management of seriously ill patients. It should be noted that there are many therapies that are being tested and that every day the information about the results obtained is changing.